Perbandingan Metode Double Moving Average dan Double Exponential Smoothing pada Peramalan Garis Kemiskinan Nusa Tenggara Timur - Tiara Risti Radamuri; Christine K. Ekowati; Ofirenty E. Nubatonis (Universitas Nusa Cendana, 2022)
The poverty line is the average expenditure to meet the needs of a decent life. The poverty line data of East Nusa Tenggara has increased, due to rice consumption as a major commodity. This forecasting is expected to provide an overview of poverty line in the future and contribute to poverty-related policy making. The data used was 22 data poverty line of East Nusa Tenggara from 2011 to 2021 (Rp/Capita/Month). The data is patterned trend, so this study will compare the double moving average and double exponential smoothing methods to forecast. The data is processed using Zaitun Time Series to get the best method. The comparison of double moving average and double exponential smoothing methods based on the similarities, the level of accuracy, and the differences were the best MAPE, forecasting results, and the efficiency of the method. Based on this comparison, the right method for forecasting the provincial poverty line (MAPE=1.755638) is double moving average. The minimum average expenditure of East Nusa Tenggara to meet the needs of decent living is Rp 443,386.58/capita/month (Mar-22), Rp 454,902.04/capita/month (Sep-22), Rp 466,417.5/capita/month (Mar-23), and Rp 477,932.96/capita/month (Sep-23). Therefore, the government can increase the popularity of local food to decrease the rice consumption.